A comparative study of histopathological findings in skin biopsies from patients with psoriasis before and after treatment with acitretin, methotrexate and phototherapy. (2nd October 2015) - Ozkanli, Seyma; Zemheri, Ebru; Karadag, Ayse Serap; Akbulak, Ozge; Zenginkinet, Tulay; Zindanci, Ilkin; Bilgili, Serap Gunes; Akdeniz, Necmettin
Abstract: Introduction : Psoriasis is a chronic and inflammatory skin disease. Few studies in the literature evaluate the responses to the treatment histopathologically. Objectives : In this study, we evaluated and compared skin biopsies taken from patients with psoriasis before and after phototherapy and therapy with acitretin and methotrexate. Material and methods : We included 64 patients with a diagnosis of psoriasis vulgaris in our study. We performed phototherapy on 33 patients (51.6%), while 19 patients (29.7%) were treated with methotrexate and 12 patients (18.8%) were treated with acitretin. Results : All of the patients had chronic plaque psoriasis, and they had skin lesions on more than 10% of their total body surface area and a score of PASI of 7.2–21.8 (average: 12.2). The histopathological parameter scores were similar in the initial evaluations of the pre-treatment treatment groups. When the biopsy specimens of all cases were evaluated together, a significant decrease was observed in terms of parakeratosis, Munro's microabscesses, regular acanthosis, pustules of Kogoj, lymphocyte infiltration in the papillary dermis, loss of the granular layer, spongiosis, suprapapillary thinning, vascularity in the papillary dermis and neutrophile infiltration in the papillary dermis. Conclusion : We found in our study that conventional treatment modalities provided histopathologically significant recovery in psoriasis, but they did not have an effect on some histopathological findings. To our knowledge, it is one of the few studies to assess these parameters in psoriasis under the continuous effect of acitretin, methotrexate and phototherapy for three months. There is a need for studies with larger series to examine the histopathological effects of these treatment modalities in terms of immunopathology.